2015
DOI: 10.1186/s12014-015-9088-3
|View full text |Cite
|
Sign up to set email alerts
|

Glycomic profiling of carcinoembryonic antigen isolated from human tumor tissue

Abstract: BackgroundCarcinoembryonic antigen (CEA) is a protein commonly found in human serum, with elevated CEA levels being linked to the progression of a wide range of tumors. It is currently used as a biomarker for malign tumors such as lung cancer and colorectal cancer [Urol Oncol: Semin Orig Invest 352: 644–648, 2013 and Lung Cancer 80: 45-49, 2013]. However, due to its low specificity in clinical applications, CEA can be used for monitoring only, rather than tumor diagnosis. The function of many glycoproteins is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 28 publications
(22 reference statements)
1
16
0
1
Order By: Relevance
“…A continuous increase in serum CEA is typically correlated with disease progression ( 75 ). Also, analytical glycoprofiling of circulating cancer-associated CEA has revealed significantly increased expression of type I and type II Lewis antigens compared to CEA from healthy individuals ( 76 ). This may possibly explain the current focus on the glycosylation status of various cancer-related protein biomarkers and on the implementation of more fucosylated epitopes (e.g., type II Lewis antigens) in the field of cancer biomarker research.…”
Section: Lewis Antigens As Cancer Biomarkersmentioning
confidence: 99%
“…A continuous increase in serum CEA is typically correlated with disease progression ( 75 ). Also, analytical glycoprofiling of circulating cancer-associated CEA has revealed significantly increased expression of type I and type II Lewis antigens compared to CEA from healthy individuals ( 76 ). This may possibly explain the current focus on the glycosylation status of various cancer-related protein biomarkers and on the implementation of more fucosylated epitopes (e.g., type II Lewis antigens) in the field of cancer biomarker research.…”
Section: Lewis Antigens As Cancer Biomarkersmentioning
confidence: 99%
“…All tissue homogenates were incubated and then centrifuged at 15,000 g for 15 min, the supernatant was kept at – 80 °C. Subsequently, the concentration of CEA was determined using Human Carcinoembryonic Antigen (CEA) ELISA Kit [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we examined glycans in colorectal carcinoma tissue samples, and identified 61 N -glycoforms present on the surface of CEA. In one of our recent studies, we showed that the composition of the glycans associated with CEA displays a considerable heterogeneity [ 19 ]. Saeland et al [ 20 ] compared CEA glycosylation patterns of normal and colorectal cancer tissues and found that Lewis X, Lewis Y, mannose and branched N -glycans are increased in tumor-associated CEA.…”
Section: Introductionmentioning
confidence: 99%
“… 9 It was reported that the levels of serum TMs showed better diagnostic values in partial malignant tumors, for example, α-fetoprotein (AFP) and prostate-specific antigen became the specific TMs of liver cancer and prostate cancer, respectively. 10 , 11 It has been demonstrated that squamous cell carcinoma antigen (SCCAg), cytokeratin 19 fragment (Cyfra21-1), and carcinoembryonic antigen (CEA) were significantly higher in cervical squamous cell carcinoma, small cell lung cancer, and colorectal carcinoma respectively; 12 14 the levels of serum Cyfra21-1 and SCCAg were significantly higher in partial patients with head and neck squamous cell carcinoma, 15 , 16 suggesting that these serum TMs might have better clinical value in the screening and diagnosis of the tumor. So far, there is still a lack of any simple or effective method to screen and diagnose patients with OSCC/OPSCC.…”
Section: Introductionmentioning
confidence: 99%